Early embolization of atrial septal defect occluder device into the left atrium - Lee, Seock Yeol (International Surgery Journal, 2023)
Atrial septal defect (ASD) is one of the most common types of congenital heart defects. Percutaneous closure of ASD is relatively safe and accepted as an alternative to surgery. However, device-related complications can occur rarely. Embolization of the Amplatzer atrial septal occluder (ASO) is one major complication of percutaneous device closure. The author presents a case of early embolization of ASO device into the left atrium, which removed the device surgically, and the ASD was closed.